Вплив препаратів нуклеїнових кислот на агрегацію тромбоцитів людини in vitro - Ткачук, З.Ю. (Видавничий дім "Академперіодика" НАН України, 2008)
In the model of aggregation of human thrombocytes induced by arachidonic acid, it has been shown that nucleic acid samples possess high antiaggregation activity. Particularly, it turned out that purified yeast RNA is highly effective and showed well-prominent characteristics in a wide range of concentrations. Sodium salt of analogous yeast RNA turned out twice as less effective and operated in a much narrower range of concentrations. This is an evidence of the antiinflaminative activity of purified yeast RNA.